2006
DOI: 10.1007/s00406-006-0681-3
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and unawareness of illness in schizophrenia

Abstract: This study investigates the impact of theory of mind (ToM) deficits on poor insight in schizophrenia. The scale for unawareness of mental disorder (SUMD) was administered to 58 stable outpatients with schizophrenia. First and second order false belief tasks, the Eyes test and a battery of nonToM cognitive measures were administered. The Second order false belief task was the best predictor of each global insight and symptom attribution scores of the SUMD. ToM tasks explained the substantial amount of the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 37 publications
8
52
1
3
Order By: Relevance
“…This findings proposed that false belief task more required cognitive effort and executive functions to perform. Consistent with these findings, other previous studies reported that ToM have strong correlated with working memory in stable schizophrenia [22] and executive function was related to concrete social cue recognition [23]. And any relation on ToM(hinting task and false belief task) with symptoms was not verified through this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This findings proposed that false belief task more required cognitive effort and executive functions to perform. Consistent with these findings, other previous studies reported that ToM have strong correlated with working memory in stable schizophrenia [22] and executive function was related to concrete social cue recognition [23]. And any relation on ToM(hinting task and false belief task) with symptoms was not verified through this study.…”
Section: Discussionsupporting
confidence: 77%
“…Our results suggest that positive and negative symptoms may not contribute to deficits of ToM. This finding may not support other reports of previous studies [22,24]. Positive symptoms were related with dose of medication.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, both second order false belief tasks (Bora et al, 2007) and metacognitive scores of an adapted version of the WSCT have shown a stronger association with insight than conventional WCST scores. Besides this general relationship between insight and ToM measures, the distinction of the 5 different insight dimensions in our study allowed identifying more specific associations.…”
Section: Lack Of a Linear Relationship Between Insight And Tom Measurmentioning
confidence: 99%
“…In this line, found that first episode schizophrenic patients' self assessment of performance on the WCST was more closely related to insight than conventional WCST scores. Similarly, Bora et al (2007) studied more directly the differential impact of ToM and executive functioning deficits on poor insight. They found that performance on second order false belief tasks was the best predictor of insight, and that WCST perseveration scores did not contribute to insight scores beyond that.…”
Section: Insight and Functional Outcomementioning
confidence: 99%